PENGARUH RETURN ON ASSETS, RETURN ON EQUITY DAN PRICE TO BOOK VALUE TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2010-2014 - Sari, Novita; Febriyani, Amelia (Program Studi Manajemen Fakultas Ekonomi Universitas Palembang, 2019)
The purpose of this study was to determine the effect of simultaneous and partial variables of financial factors consisting of Return on assets, Return on Equity and Price to Book Value affect the Stock Price. The population in this study is the financial statements of manufacturing companies listed on the Indonesia Stock Exchange. The sampling technique was carried out by means of the purposive sampling method and obtained 15 companies as research samples. The observation period is 5 years, 2010-2014 so that the unit of analysis obtained is 75 financial statements of listed manufacturing companies. The research variables consist of independent variables in the form of Return on Assets (X1), Return on Equity (X2) and Price to Book Value (X3) and Stock Price (Y) as the dependent variable. Data collection method in this research is documentation method. Data analysis technique used is multiple linear regression. Based on the results of the regression analysis it is known that the effect of Return on assets, Return on Equity and Price to Book Value simultaneously affect the stock price on the IDX by 96.3% while the remaining 3.7% is influenced by other variables not examined in this study. Partially, Return on assets and Price to Book Value have a significant effect on stock prices, while Return on Equity has an effect but not significantly on stock prices.